Preserving the Acehnese Language Through Qanun and Educational Synergy - Santika, Cut; Hidayani, Novita (Indonesian Journal of Education Methods Development, 2025)
General Background: The Acehnese language, as a crucial symbol of cultural identity, faces the threat of extinction due to globalization, modernization, and linguistic dominance. Specific Background: Despite Aceh’s legal efforts through Qanun No. 10 of 2022 and Qanun No. 11 of 2014 mandating the inclusion of the Acehnese language in education, implementation challenges persist in Bireuen City. Knowledge Gap: Previous studies rarely assess how effectively these qanun-based policies interact with educational practices to sustain language vitality. Aims: This study analyzes the effectiveness of qanun and educational policies in preventing the extinction of the Acehnese language as a form of local wisdom in Bireuen City. Results: Using mixed methods, findings reveal strong student awareness and positive attitudes toward language preservation, yet implementation remains weak due to a shortage of qualified teachers, limited instructional materials, minimal teaching hours, and low curricular innovation. Family and community support play a key role in maintaining linguistic continuity. Novelty: This study highlights the disjunction between normative regulation and practical implementation, emphasizing students’ and teachers’ cultural commitment as assets for language revitalization. Implications: Strengthening teacher certification, curriculum development, and digital integration is essential to transform qanun from symbolic policy into an effective instrument for preserving Acehnese linguistic heritage. Highlights: Qanun implementation remains weak despite strong cultural awareness. Teachers and families act as key agents of language preservation. Digital innovation is vital for sustaining Acehnese language vitality. Keywords: Qanun, Education Policy, Acehnese Language, Local Wisdom, Language Preservation